The Relationship between Social Media Addiction, Hardiness, and Emotional Intelligence with Students' Psychological Well-Being - Saputri, Fristya Qusnul; Purwanto, Edy; Ahmadi, Farid (Jurnal Bimbingan Konseling, 2024)
Low adolescent psychological well-being will have an impact on the lack of fulfilment of his psychological needs and bring up negative emotions. Thus, the present study attempted to analyze the relationship between social media addiction, hardiness, and emotional intelligence with psychological well-being and their implications for guidance and counselling. It used a correlational design with a sample of 335 students selected using the cluster proportionate stratified random sampling technique. Students’ data were collected using the Social Media Addiction Scale (SMAC) for the social media addiction, the DRS15 scale (Dispositional Resilience Scale: a short hardiness measure) for the hardiness, the Trait Emotional Intelligence Questionnare-Adolescent Short Form (TEIQue-ASF) scale for emotional intelligence, and the psychological well-being scale. The Findings showed that there was a relationship between social media addiction, hardiness, and emotional intelligence with psychological well-being. Thus, school counselors can make use of hardiness and emotional intelligence to improve psychological well-being through guidance and counseling services.